Assessing the Use of Artificial Hibernacula by the Great Crested Newt (Triturus cristatus) and Smooth Newt (Lissotriton vulgaris) in Cold Climate in Southeast Norway - Børre K. Dervo; Jon Museth; Jostein Skurdal (Diversity, 2018)
Construction of artificial overwintering habitats, hibernacula, or newt hotels, is an important mitigation measure for newt populations in urban and agricultural areas. We have monitored the use of four artificial hotels built in September 2011 close to a 6000 m2 breeding pond in Norway. The four hotels ranged from 1.6 to 12.4 m3 and were located from 5 to 40 m from the breeding pond. In 2013–2015, 57 Great Crested Newts (Triturus cristatus) and 413 Smooth Newts (Lissotriton vulgaris) spent the winter in the hotels. The proportions of juveniles were 75% and 62%, respectively, and the hotels may be important to secure recruitment. Knowledge on emigration routes and habitat quality for summer use and winter hibernation is important to find good locations for newt hotels. The study documented that newts may survive a minimum temperature of −6.7 °C. We recommend that newt hotels in areas with harsh climate are dug into the ground in slopes to reduce low-temperature exposure during winter.